»Zavedajmo se pri vsaki naši akciji, da tekmujemo!« - Guštin, Damijan (Prispevki za novejšo zgodovino, 2024)
In the summer and autumn of 1944, the leadership of the resistance movement in Slovenia held two competitions among its political bodies and military units. Based on primary sources, the article analyses the idea, implementation, and results of these competitions, which, in terms of their content, represented a synergy between the resistance movement’s motivational and propaganda approaches and its needs for additional material resources and the expansion of its personnel. The competitions in gathering the material and political support for the resistance organisation spurred the further activation of its political bodies at all levels and encouraged a better definition of their political tasks. Obtaining additional material and human resources directly from the population was vital for the functioning and survival of the resistance organisation under the conditions of significant deficit. However, such actions could only be carried out in the areas where the resistance was sufficiently organised and which were not entirely controlled by the occupying forces and their collaborators.
Keywords: competition; druga svetovna vojna; Liberation Front of the Slovenian Nation; motivation; motiviranje; odporniško gibanje; Osvobodilna fronta slovenskega naroda; propaganda; resistance; Slovenija; tekmovanje; World War II